Controlling the fluorescence properties of nitrogen vacancy centers in nanodiamonds. Issue 4 (10th January 2019) - Laube, Christian; Oeckinghaus, Thomas; Lehnert, Jan; Griebel, Jan; Knolle, Wolfgang; Denisenko, Andrej; Kahnt, Axel; Meijer, Jan; Wrachtrup, Jörg; Abel, Bernd
Abstract : Controlled enhancement of NV center fluorescence in nanodiamonds via control over the formation process and surface parameters. Abstract : Control over the formation and fluorescence properties of nitrogen vacancy (NV) centers in nanodiamonds (NDs) is an important factor for their use in medical and sensor applications. However, reports providing a deep understanding of the potential factors influencing these properties are rare and focus only on a few influencing factors. The current contribution targets this issue and we report a comprehensive study of the fluorescence properties of NVs in nanodiamonds as a function of electron irradiation fluence and surface termination. Here we show that process parameters such as defect center interactions, in particular, different nitrogen defects and radiation induced lattice defects, as well as surface functionalities have a strong influence on the fluorescence intensity, fluorescence lifetime and the charge state ratio of the NV centers. By employing a time-correlated single photon counting approach we also established a method for fast macroscopic monitoring of the fluorescence properties of ND samples. We found that the fluorescence properties of NV centers may be controlled or even tuned depending upon the radiation treatment, annealing, and surface termination.